Correlation between Maternal Systemic Inflammatory Indicators before Delivery and Congenital Pneumonia in Newborns: A Case-Control Study - Tianping Bao; Bingrui Yu; Yu Chen; Yuan Zhang; Huaiping Cheng; Zhaofang Tian (MDPI AG, 2024)
Background: Congenital pneumonia is a common respiratory disease in newborns, often influenced by obstetric factors. Clinical diagnosis can be delayed, prompting interest in using systemic inflammatory indicators to predict various diseases. Objective: Our aim was to evaluate the predictive value of maternal systemic inflammatory indicators before delivery for congenital pneumonia in newborns. Methods: This retrospective study included full-term, singleton infants born at the Affiliated Huaian No. 1 People's Hospital of Nanjing Medical University between January 2017 and December 2022. Infants admitted to the neonatal department within 48 h of birth were divided into two groups: 46 with clinical congenital pneumonia (the observation group) and 65 without congenital pneumonia (the control group). Maternal peripheral blood, complete blood cell count, and general condition within 72 h before delivery, as well as neonatal admission data were recorded. Systemic inflammatory indicators were assessed. Receiver operating characteristic curves were used to evaluate the predictive value of the maternal systemic inflammatory indicators before delivery for congenital pneumonia. A prediction model for neonatal pneumonia was constructed by combining systemic inflammatory indicators before delivery with logistic regression. The association between this prediction model and the prognosis of neonatal congenital pneumonia was examined. Results: Maternal systemic inflammatory indicators before delivery as predictive markers for congenital pneumonia and the regression model jointly constructed by NLR, MLR, SII, SIRI, and PIV before delivery predicted the occurrence of congenital pneumonia better. Maternal systemic inflammatory indicators correlated with the severity of congenital pneumonia in neonates. Conclusions: Maternal systemic inflammatory indicators before delivery have predictive value for congenital pneumonia in neonates, aiding early identification and treatment.